Placebo‐like analgesia via response imagery. (19th April 2017) - Peerdeman, K.J.; van Laarhoven, A.I.M.; Bartels, D.J.P.; Peters, M.L.; Evers, A.W.M.
Abstract: Background: Placebo effects on pain are reliably observed in the literature. A core mechanism of these effects is response expectancies. Response expectancies can be formed by instructions, prior experiences and observation of others. Whether mental imagery of a response can also induce placebo‐like expectancy effects on pain has not yet been studied systematically. Methods: In Study 1, 80 healthy participants were randomly allocated to (i) response imagery or (ii) control imagery. In Study 2, 135 healthy participants were randomly allocated to (i) response imagery with a verbal suggestion regarding its effectiveness, (ii) response imagery only, or (iii) no intervention. In both studies, expected and experienced pain during cold pressor tests were measured pre‐ and post‐intervention, along with psychological and physiological measures. Results: Participants rated pain as less intense after response imagery than after control imagery in Study 1 ( p = 0.044, η p 2 = 0.054) and as less intense after response imagery (with or without verbal suggestion) than after no imagery in Study 2 ( p < 0.001, η p 2 = 0.154). Adding a verbal suggestion did not affect pain ( p = 0.068, η p 2 = 0.038). The effects of response imagery on experienced pain were mediated by expected pain. Conclusions: Thus, in line with research on placebo effects, the current findings indicate that response imagery can induce analgesia, via its effects on response expectancies. Significance: The reported studies extend research on placebo effects by demonstrating that mental imagery of reduced pain can induce placebo‐like expectancy effects on pain.